Production of tartary buckwheat distilled spirits through enrichment of flavonoids in buckwheat distiller's grains - ZHANG Pengjie, GAN Linyao, SUN Jinxu, GUO Kaikai, CHEN Yefu, XIAO Dongguang, GUO Xuewu (Zhongguo niangzao)
Tartary buckwheat is rich in bioflavonoids, due to its high boiling point, it remains in the distiller's grains when brewing Baijiu. In this study, tartary buckwheat distilled spirits was prepared by tartary buckwheat and rice fermentation. The extraction and purification processes of flavonoids from tartary buckwheat distilled spirits were optimized using single-factor and orthogonal experiments. The purified flavonoid extract was added to the distilled spirits, and a preparation scheme of tartary buckwheat distilled spirits rich in flavonoids was determined through sensory evaluation. The results showed that the optimal ultrasound extraction process of flavonoids from tartary buckwheat fermented grains was as follows: ultrasonic power 600 W, ethanol volume fraction 90%, solid-liquid ratio 1∶30 (g∶ml), and ultrasonic time 50 min. Under these conditions, the yield of total flavonoids was 0.9% and the purity was 38.3%. The purification process of flavonoids in tartary buckwheat distiller's grains using macroporous resin was pH=4, sample loading flow rate 2 ml/min, sample concentration 0.2 mg/ml, 70% ethanol 50 ml, and elution flow rate 11 ml/min. The purity of tartary buckwheat distiller's grain flavonoid extract prepared by this process was 85.36%. The optimal preparation scheme of tartary buckwheat distilled spirits was to add the purified flavonoid extract to the distilled spirits, resulting in a total flavonoid extract content of 400-600 mg/L, which provided the optimal evaluation score for the compound tartary buckwheat distilled spirits. Under the optimized process, high-purity flavonoid extracts could be obtained, and the compound tartary buckwheat distilled spirits had a distinct buckwheat aroma, soft texture, and harmonious flavor due to the rich content of flavonoids.